Study on Energy and Biofuels Generation from Biomass through Thermochemical Conversion Technologies - Tsatiris, Michael; Kitikidou, Kiriaki (Current Approaches in Science and Technology Research Vol. 1, 2021)
Biomass, as a renewable source of energy, could be converted into fuel in solid, liquid or gaseous form through a variety of modern technological production methods. Thermochemical processes and conversion technologies are briefly described in this paper with special emphasis on direct combustion and pyrolysis. The use of wood for energy purposes is becoming increasingly attractive in Greece and for the Mediterranean ecosystems as it can be upgraded into a more valuable and usable fuel. In addition, technologies are being developed for densifying biomass into briquettes or pellets which can be easily and economically transported.